2017
DOI: 10.1111/ajo.12604
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and training of obstetrics and gynaecology trainees in Australia and New Zealand

Abstract: Fatigue was frequently reported by RANZCOG trainees with increased working hours and long shifts being significant factors in fatigue levels. Strategies should be developed and trialled to enable trainees to obtain adequate case exposure and teaching without compromising patient and doctor safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…For instance, various studies before the emergence of COVID-19 have shown that fatigued doctors are at high risk of having commuting accidents [ 14 ], contracting needlestick injury [ 15 ], making diagnostic, medical and clinical errors [ 16 , 17 ], and experiencing poor recovery [ 10 ]. Fatigue among doctors is also associated with less enjoyment in work [ 18 ] and high turnover intention [ 19 ]. Other consequences include adverse health and wellbeing, work-life dissatisfaction, low quality of life, job dissatisfaction, and poor skill performance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, various studies before the emergence of COVID-19 have shown that fatigued doctors are at high risk of having commuting accidents [ 14 ], contracting needlestick injury [ 15 ], making diagnostic, medical and clinical errors [ 16 , 17 ], and experiencing poor recovery [ 10 ]. Fatigue among doctors is also associated with less enjoyment in work [ 18 ] and high turnover intention [ 19 ]. Other consequences include adverse health and wellbeing, work-life dissatisfaction, low quality of life, job dissatisfaction, and poor skill performance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…No fatigue, no dozing and no regrets; still doing around 50 h per week at age 72 years. I cannot support the ideas projected by the four authors …”
mentioning
confidence: 85%
“…Although the principle is under challenge, the broad tenet does explain why any one person can only properly master one, or at best a few related activities in their lifetime. With this in mind I was bemused by the recent articles in the October issue of ANZJOG dealing with the working hours of trainees in obstetrics and gynaecology where a 53.1 h working week was projected as dangerous for both patients and doctors.…”
mentioning
confidence: 99%
“…Irregular working hours with associated fatigue, high patient expectations, management of life‐threatening emergencies and litigation threats have been identified as causing moderate to very high stress in trainees . Furthermore, sleep deprivation and significant workload are common, with 72.9% of RANZCOG trainees feeling regularly or always fatigued; with an association observed between level of reported fatigue and the number of hours worked per week . The average working hours for RANZCOG trainees is 53.1 h/week .…”
Section: Introductionmentioning
confidence: 99%